1978
DOI: 10.1159/000148969
|View full text |Cite
|
Sign up to set email alerts
|

Non-A, Non-B Hepatitis Transmission in Chimpanzees: A Project of the Transfusion-Transmitted Viruses Study Group

Abstract: Experimental transmission of non-A, non-B hepatitis was apparently accomplished in 5 chimpanzees following inoculation with presumably infectious human sera. Administration of sera from implicated donors with normal alanine aminotransferase (ALT) values, as well as from those with abnormal ALT levels, resulted in the development of ALT abnormalities in the inoculated chimpanzees. Transmission from donors with normal ALT values implies that healthy carriers of non-A, non-B virus exist. Evidence is presented whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(31 citation statements)
references
References 5 publications
0
29
0
1
Order By: Relevance
“…With the advent of serological tests to detect infection by HAV and HBV in the mid-1970s, it was surprising to find that most cases of parenterally-transmitted hepatitis were not in fact due to either virus [4] hence heralding the term, Non-A, Non-B hepatitis (NANBH). Dr. Harvey Alter and other groups then pioneered the use of the chimpanzee as a reliable model for serial passage of NANBH infection from human materials [5,6]. The use of this model provided data indicating the existence of multiple NANBH agents, one of which was shown to cause characteristic membranous tubules within the cytoplasm of infected chimpanzee hepatocytes (the so-called tubule-forming agent (TFA; Ref.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of serological tests to detect infection by HAV and HBV in the mid-1970s, it was surprising to find that most cases of parenterally-transmitted hepatitis were not in fact due to either virus [4] hence heralding the term, Non-A, Non-B hepatitis (NANBH). Dr. Harvey Alter and other groups then pioneered the use of the chimpanzee as a reliable model for serial passage of NANBH infection from human materials [5,6]. The use of this model provided data indicating the existence of multiple NANBH agents, one of which was shown to cause characteristic membranous tubules within the cytoplasm of infected chimpanzee hepatocytes (the so-called tubule-forming agent (TFA; Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to study the various aspects of this serious human disease, chimpanzees have been shown to be suitable experimental models that are susceptible to NANB hepatitis virus infection (2,3,16,17,24). The reagent materials (NANB antigen) obtained from experimental animals have been used in conjunction with presumed convalescent human antibody to NANB in attempts to demonstrate immunological reactions with specificity for NANB hepatitis antigen.…”
mentioning
confidence: 99%
“…The existence of the NANB hepatitis viruses became evident from epidemiological studies [Alter et al, 1978;Tabor et al, 19781 as well as by inoculation of human volunteers [Hoofnagle et al, 19771 and chimpanzees [Alter et al, 1978;Tabor et al, 1978;Hollinger et al, 1978;Bradley et al, 19801. Further cross-challenge experiments in chimpanzees indicated that there are, at least, two parenterally transmitted viruses [Shimizu et al, 1979;Bradley et al, 1980;Hollinger et al, 1980;Yoshizawa et al, 19811.…”
Section: Introductionmentioning
confidence: 99%